Perspectives On International Political Economy: Labor and Environmental Standards Should Be in World Trade Organizations? - Selin Çınar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The concept of sustainable development and environmental protection are among the main objectives of the World Trade Organization. For this purpose, the labor and environmental standards of the World Trade Organization are also included in the agreement. In 1994, the World Trade Organization Trade and Environment Committee was established in this context, and international organizations joined it. So, in this paper analyze that labor and environmental standards should be in a Trade Organization unbiased way. This study examines the complex rhetoric surrounding the incorporation of labor and environmental norms into the World Trade Organization (WTO) structure. The phenomenon of trade globalization has profoundly affected the interdependence of economies, prompting inquiries into the ethical aspects of international commerce. Incorporating labor and environmental norms into the World Trade Organization (WTO) has emerged as a central topic of controversy. Advocates contend that incorporating such measures is paramount in promoting sustainable growth, guaranteeing equitable labor standards, and addressing global environmental deterioration. However, integrating these standards could impose economic constraints, impede the free trade flow, and even result in the adoption of protectionist measures. This study explores multiple viewpoints, evaluates the possible consequences, and evaluates the practicality of integrating labor and environmental concerns within the World Trade Organization (WTO). This study makes a valuable contribution to the continuing discourse surrounding the development of a more inclusive and responsible international political economy by assessing its effects on economic growth, social justice, and environmental sustainability.